Myocilin Regulates Cell Proliferation and Survival - Joe, Myung Kuk (American Society for Biochemistry and Molecular Biology, 2014)
Myocilin, a causative gene for open angle glaucoma, encodes a secreted glycoprotein with poorly understood functions. To gain insight into its functions, we produced a stably transfected HEK293 cell line expressing myocilin under an inducible promoter and compared gene expression profiles between myocilin-expressing and vector control cell lines by a microarray analysis. A significant fraction of differentially expressed genes in myocilin-expressing cells was associated with cell growth and cell death, suggesting that myocilin may have a role in the regulation of cell growth and survival. Increased proliferation of myocilin-expressing cells was demonstrated by the WST-1 proliferation assay, direct cell counting, and immunostaining with antibodies against Ki-67, a cellular proliferation marker. Myocilin-containing conditioned medium also increased proliferation of unmodified HEK293 cells. Myocilin-expressing cells were more resistant to serum starvation-induced apoptosis than control cells. TUNEL-positive apoptotic cells were dramatically decreased, and two apoptotic marker proteins, cleaved caspase 7 and cleaved poly(ADP-ribose) polymerase, were significantly reduced in myocilin-expressing cells as compared with control cells under apoptotic conditions. In addition, myocilin-deficient mesenchymal stem cells exhibited reduced proliferation and enhanced susceptibility to serum starvation-induced apoptosis as compared with wild-type mesenchymal stem cells. Phosphorylation of ERK1/2 and its upstream kinases, c-Raf and MEK, was increased in myocilin-expressing cells compared with control cells. Elevated phosphorylation of ERK1/2 was also observed in the trabecular meshwork of transgenic mice expressing 6-fold higher levels of myocilin when compared with their wild-type littermates. These results suggest that myocilin promotes cell proliferation and resistance to apoptosis via the ERK1/2 MAPK signaling pathway.